Histori dan Visi Gereja Karismatis - Yuwono, Moses William (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
This article seeks to participate in the efforts to revitalize the charismatic dimension within the Church. After centuries of being overly cerebral, the Holy Spirit breathed a new stream of grace in the 20th century. The Catholic Charismatic Renewal Movement, in its own way, interprets the will of the Holy Spirit by vivifying faith in a more cordial manner. Through literature examination, both Church documents and theological works, the author elaborates the journey of this recently overflowing new charismatic consciousness in the Church, as well as the vision of the Church leaders regarding a more charismatic future of the Church. There are many virtuous fruits that have been produced by the Renewal stirred by the Holy Spirit, that the popes argue it would be regrettable if they were not involved in realizing a more vibrant future of the Church. In the end, not only the members of the Renewal are invited to be charismatic but the entire Church must be charismatic in its character. For that reason, the members of the Renewal are expected to be more engaged in the Church’s ministry, and the Church can also be more open in adopting the good practices of the Renewal.